Beluga (D. leucas), harbor porpoise (P. phocoena), and killer whale (O. orca) acoustic presence in kotzebue sound, alaska: Silence speaks volumes - Castellote, Manuel; Small, Robert J.; Stafford, Kathleen M.; Whiting, Alex; Frost, Kathryn J. (Frontiers in Remote Sensing, 2022)
Prior to 1984, belugas (Delphinapterus leucas) were seen in large numbers during spring and summer in Kotzebue Sound, Alaska, and provided an important subsistence resource to coastal residents. Sightings and harvest declined sharply beginning in 1984: the average annual harvest dropped from 84/yr (1977–1983) to 16/yr (1984–2021). To examine the current seasonal and spatial occurrence of belugas in Kotzebue Sound, passive acoustic moorings were deployed in summer 2013 and year-round in 2014–2016. Three moorings were deployed off Cape Krusenstern, northwestern Kotzebue Sound, to monitor cetaceans traveling nearshore. A mooring was also deployed near Chamisso Island, southeastern Kotzebue Sound. We used automatic detectors to process the recordings for echolocation and tonal signals, and all detections were manually validated. Belugas, harbor porpoises (Phocoena), and transient killer whales (Orcinus orca) were detected in both areas, primarily from June to November. Detections extended into early winter for belugas, and sporadic detections were confirmed for porpoises from January to March. Belugas were detected on a total of 20 days, killer whales on 96 days, and porpoises on 179 days. All beluga detections were echolocation signals; the absence of social signals likely reflects an anti-predator response to transient killer whales and possibly to subsistence hunters. Killer whale detections were composed of echolocation signals, limited to very short click trains, double clicks, and single clicks, a known cryptic acoustic behavior used when targeting prey. Killer whales also emitted high frequency whistles (17–51 kHz) providing the first evidence of these types of signals for transients. Our results suggest transient killer whales in predation mode scouting harbor porpoise and beluga habitat, concurrent with belugas in silent anti-predation mode. This anti-predation acoustic behavior by belugas was also evident when killer whales were not present, conveying a continued perception of predation risk for this habitat. The combined natural and anthropogenic predation pressure in Kotzebue Sound could be playing an important role in the continued low occurrence of belugas.